Global value perceptions: The legitimising functions of western representations of democracy. (December 2015) - Staerklé, Christian; Falomir‐Pichastor, Juan Manuel; Pereira, Andrea; Berent, Jacques; Butera, Fabrizio
Abstract: This paper argues that a fundamental antagonism between democracy and nondemocracy organises lay thinking on global issues. We review key findings of a long‐standing experimental research programme that examined the " Democracy‐as‐value " hypothesis across a variety of political and social contexts. This hypothesis contends that democracy is an ideological belief system that provides value to democratic individuals, groups, and institutions and thereby grants legitimacy to their actions. Based on procedural justice theories and social representations theory, we contend that western lay perceivers associate democracy with procedural equality and individual autonomy, whereas nondemocracy is associated with ingroup hierarchy and conformity. We discuss how idealised representations of democracy justify global power arrangements and emphasise the paradoxical justification function of democratic values through which nondemocratic forms of social regulation based on physical force are legitimised with the very democratic norms that call for peaceful resolution of conflicts.